Monetary policy and exchange rate interactions in a small open economy - Hilde C. Bjørnland (University of Oslo, Department of Economics, 2005)
This paper analyses the transmission mechanisms of monetary policy in a small open economy like Norway through structural VARs, paying particular attention to the interdependence between the monetary policy stance and exchange rate movements in the inflation-targeting period. Previous studies of the effects of monetary policy in open economies have typically found small or puzzling effects on the exchange rate; puzzles that may arise due to the recursive restrictions imposed on the contemporaneous interaction between monetary policy and the exchange rate. By instead imposing a long-run neutrality restriction on the real exchange rate, thereby allowing the interest rate and the exchange rate to react simultaneously to any news, the interdependence increases considerably. In particular, following a contractionary monetary policy shock, the real exchange rate appreciates immediately and thereafter depreciates back to baseline. Furthermore, output and consumer price inflation fall gradually as expected; thereby also ruling out any price puzzle that has commonly been found in the literature. Results are compared and found to be consistent with among other the findings from an “event study” that focuses on immediate responses in asset prices following a surprise monetary policy decision.
Keywords: C32; E52; F31; F41; 330; VAR; monetary policy; open economy; identification; event study.; VAR-Modell; Geldpolitik; Wechselkurs; Kleines-offenes-Land; Norwegen